𝑝-Carleson Measures for a Class of Hardy-Orlicz Spaces - Benoît Florent Sehba (International Journal of Mathematics and Mathematical Sciences)
An alternative interpretation of a family of weighted Carleson measures is used to characterize 𝑝-Carleson measures for a class of Hardy-Orlicz spaces admitting a nice weak factorization. As an application, we provide with a characterization of symbols of bounded weighted composition operators and Cesàro-type integral operators from these Hardy-Orlicz spaces to some classical holomorphic function spaces.